2023
DOI: 10.1097/pg9.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ANO1 Gene Variant is Associated with Intestinal Dysmotility Syndrome Masquerading as Hirschsprung Disease: A Case Report

Abstract: Anoctamin 1 (ANO1)-related intestinal dysmotility syndrome (OMIM: 620045) is an extremely rare disorder with only 2 cases reported in the medical literature. We present the clinical scenario of a 2-month-old male infant that presented to our center with diarrhea, vomiting, and abdominal distension. Routine investigations did not yield a clear diagnosis. Whole-exome sequencing showed a novel homozygous nonsense ANO1 pathogenic variant (c.1273G>T) with a protein alternation of p.Glu425Ter that fits the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…The broad spectrum of tissue expression explains the wide range of disorders associated with their respective disrupted function. Several ANO family members have been associated with a variety of human diseases or increased risks for diseases such as intestinal dysmotility (MIM: 620045 ) 31 , 32 and moyamoya disease (MIM: 620687 ) 33 with ANO1 , dystonia (MIM: 615034 ) 34 , 35 with ANO3 , gnathodiaphyseal dysplasia (MIM: 166260 ) 36 , 37 , 38 , 39 and muscular dystrophies (MIM: 613319 , 611307 ) 40 , 41 , 42 , 43 , 44 with ANO5 , disturbed blood coagulation (Scott syndrome, MIM 262890 ) 24 , 45 with ANO6 , spinocerebellar ataxia (MIM: 613728 ) 46 , 47 , 48 with ANO10 , and pancreatic and colorectal cancer 49 , 50 with ANO9 . ANO4 has not been linked to a Mendelian phenotype so far, but genome-wide association studies showed an association between single-nucleotide polymorphisms near ANO4 and various neurological diseases, such as schizophrenia, Alzheimer disease, and anxiety disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad spectrum of tissue expression explains the wide range of disorders associated with their respective disrupted function. Several ANO family members have been associated with a variety of human diseases or increased risks for diseases such as intestinal dysmotility (MIM: 620045 ) 31 , 32 and moyamoya disease (MIM: 620687 ) 33 with ANO1 , dystonia (MIM: 615034 ) 34 , 35 with ANO3 , gnathodiaphyseal dysplasia (MIM: 166260 ) 36 , 37 , 38 , 39 and muscular dystrophies (MIM: 613319 , 611307 ) 40 , 41 , 42 , 43 , 44 with ANO5 , disturbed blood coagulation (Scott syndrome, MIM 262890 ) 24 , 45 with ANO6 , spinocerebellar ataxia (MIM: 613728 ) 46 , 47 , 48 with ANO10 , and pancreatic and colorectal cancer 49 , 50 with ANO9 . ANO4 has not been linked to a Mendelian phenotype so far, but genome-wide association studies showed an association between single-nucleotide polymorphisms near ANO4 and various neurological diseases, such as schizophrenia, Alzheimer disease, and anxiety disorder.…”
Section: Introductionmentioning
confidence: 99%
“… 57 Furthermore, ANO4 was found upregulated in human tumor samples compared to normal kidney tissue, suggesting a potential role as a prognostic biomarker in non-metastasized clear cell renal cell carcinoma. 31 …”
Section: Introductionmentioning
confidence: 99%